EFEKTIVITAS PENGAWASAN LALU LINTAS MELALUI SURABAYA INTELLIGENT TRANSPORT SYSTEM (SITS) DI KOTA SURABAYA - Delia Fahriana Sahira; Suci Megawati (Universitas Negeri Surabaya, 2022)
The use of technology in government or E-Government has been applied to support the service process to the community. Surabaya is a city that has pioneered the implementation of e-government since 2002. With the issuance of Surabaya Mayor Regulation Number 5 of 2013 concerning Guidelines for the Utilization of Information and Communication Technology In the Implementation of Local Government, the Surabaya City Transportation Service creates a system that aims to improve security, reduce congestion, monitor traffic by creating Surabaya Intelligent Transport System (SITS). The purpose of this study is to describe the effectiveness of traffic control through the Surabaya Intelligent Transport System (SITS) in Surabaya. This study is a descriptive qualitative approach that focuses on explaining whether the program has been effective in accordance with the objectives that have been set. The theory used in this research is the theory of effectiveness according to Gibson which has 5 (five) indicators, namely production, efficiency, satisfaction, adaptability and development. The data collection techniques used are through interviews, observation and documentation, while the data analysis techniques use an interactive model according to Miles and Huberman, namely data collection, data reduction, data presentation and drawing conclusions. The results of this study indicate that the implementation of SITS on the production indicators is quite optimal, the efficiency indicators of SITS are quite efficient in breaking down congestion, the satisfaction indicators of SITS are sufficient to meet the satisfaction criteria, the adaptation indicators are quite good but there is still a lack of socialization, the development indicators are quite good and helped by the existence of application. So the researchers suggest to focus on socializing and improving application performance. Keywords: Effectiveness, supervision, traffic jam, SITS Surabaya City